Transport as a Factor in the Investment Climate - Aoki, Naomi; Roberts, Peter (World Bank, Washington, DC, 2012)
This Note shows how, through a process of consultation between the World Bank Transport Sector and Private Sector Department, some focus on transport has been introduced into the Global "core" module of the Investment Climate Survey. The Note also shows the scope for achieving much more focus on specific transport constraints in Investment Climate Assessments for countries where these are expected to be particularly important. Examples are given of questionnaires which have been developed to complement the "core" module and specifically to meet the needs of two Regions, Africa and Latin America and the Caribbean, where different aspects of transport have been identified as significant considerations for investors. For Africa the focus is on the availability of suitable transport services. For Latin America the emphasis is rather on the role of transport in influencing the location of enterprises. Application of these revised questionnaires will provide more data on the contribution of transport to doing business in different countries.